Montreal Cognitive Assessment (MoCA) use in general practice for the early detection of cognitive impairment: a feasibility study - Cassandre Carton; Matthieu Calafiore; Charles Cauet; Nassir Messaadi; Marc Bayen; David Wyts; Wassil Messaadi; Teddy Richebe; Sabine Bayen (BJGP Open)
Background: GPs can detect cognitive impairment (CI) at a very early stage, allowing early support for people and their caregivers. The early onset of CI is between 50 years and 60 years. Currently, in France, the Mini-Mental State Examination (MMSE) remains the most used screening test, although it has a lower sensitivity and specificity than the Montreal Cognitive Assessment (MoCA) for detecting mild CI, taking an average of 15 minutes to complete. Aim: To investigate the feasibility of the MoCA during routine consultations in general practice for the early detection of CI and to determine prevalence of CI in a primary care setting. Design & setting: A quantitative, prospective feasibility study was carried out in real-life working conditions during routine GP consultations in France. Method: GPs performed MoCA on adults aged ≥50 years, without suspected or confirmed CI. Results: Sixty-one GPs performed 221 MoCA with a mean duration of 8 minutes and detected mild neurocognitive impairment in 62% of patients. Conclusion: The MoCA is feasible and easy to perform during routine consultations in general practice by trained and experienced physicians.